The presence of a secondary caregiver differentiates primary cancer caregiver well-being - Thomson, Maria D.; Wilson-Genderson, Maureen; Siminoff, Laura A. (Supportive care in cancer, 2022)
Background Informal caregivers play a fundamental role in the care of hematological cancer patients, but less is known about how secondary caregivers are involved. We assessed the presence or absence of a secondary caregiver, the types of caregiving activities performed by primary and secondary caregivers, and examined whether the presence of a secondary caregiver was associated with primary caregiver characteristics and well-being over time. Methods A case series of hematological cancer patient-caregiver dyads ( n = 171) were recruited from oncology clinics in Virginia and Pennsylvania and followed for 2 years. Multilevel models were developed to examine the associations between the presence of a secondary caregiver and the primary caregivers’ well-being. Results Most (64.9%) primary caregivers reported having secondary caregivers. Multilevel models showed primary caregivers without help had higher baseline mental and physical health, but experienced deteriorating physical health over time, compared to supported primary caregivers. Supported primary caregivers reported improvements in mental health over time that was associated with improvements in physical health. Conclusions Primary caregivers in good physical and mental health at the beginning of their caregiving journey but who have the least assistance from others may be at greatest risk for detrimental physical health effects long term. Attention to the arrangement of caregiving roles (i.e., who provides what care) over time is needed to ensure that caregivers remain healthy and well supported.